Physicochemical Studies on L-Cell Virions - Nichols, J. L. (1973)
The L-cell virion (LCV) has been purified from supernatant fluids of mouse L cells grown in suspension culture. The virion is similar to other RNA tumor viruses by several criteria: (i) the density of the virion is 1.16 g/cm(3); (ii) the virion appears as a rounded membranous particle with an outer diameter of 146.7 ± 11.8 nm, and contains knobs (7-nm diameter) over its surface; (iii) 15 polypeptides (ranging in molecular weight from 7,000 to 110,000) are detectable after electrophoresis of virion protein in sodium dodecyl sulfate-polyacrylamide gels; (iv) three species of RNA can be isolated—high molecular weight (80 to 88s) (50%), 7s (35%) and 4s (15%); (v) heat denaturation of the high-molecular-weight RNA yields a heterogeneous population of molecules (20 to 35s) as well as a 7s and 4s species. Despite the general similarity to infectious RNA tumor viruses, LCV is apparently defective as evidenced by the fact that it does not induce tumors in animals or transform normal mouse cells in vitro (Kindig and Kirsten [17]). The defective nature of the LCV might be related to the fact that assays for DNA polymerase in the virion showed only a negligible activity when compared to Rous sarcoma virus.